Bubble dynamics in laser lithotripsy - Mohammadzadeh, Milad (2018)
Laser lithotripsy is a medical procedure for fragmentation of urinary stones with a fiber guided laser pulse of several hundred microseconds long. Using high-speed photography, we present an in-vitro study of bubble dynamics and stone motion induced by Ho:YAG laser lithotripsy. The experiments reveal that detectable stone motion starts only after the bubble collapse, which we relate with the collapse-induced liquid flow. Additionally, we model the bubble formation and dynamics using a set of 2D Rayleigh-Plesset equations with the measured laser pulse profile as an input. The aim is to reduce stone motion through modification of the temporal laser pulse profile, which affects the collapse scenario and consequently the remnant liquid motion.